EVALUATION OF COMMUNITY DEVELOPMENT IMPLEMENTATION IN PRACTICUM II SOCIAL WELFARE STUDENTS OF UIN SYARIF HIDAYATULLAH JAKARTA IN THE COVID-19 PANDEMIC - Nurkhayati, Nurkhayati; Habibie, Fithratullah; Kharima, Nadya (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2021)
Abstract. The impact of the COVID-19 pandemic has been acknowledged abruptly changing various systems of human life, including the line of education which is the most important part of the human core. This also includes the line of education in the field of social welfare which has an impact on the implementation of community development which is usually carried out in the midst of the community or commonly referred to as practicum ii (two). Even though in the end, the students of the Social Welfare Study Program at UIN Syarif Hidayatullah Jakarta still had to carry out during the COVID-19 pandemic. Therefore, researchers intend to evaluate the implementation of community development in practicum II for social welfare students at Syarif Hidayatullah University Jakarta during the COVID-19 pandemic. Research that uses this approach looks at various informants' perspectives which is carried out by FGD (Focus Group Discussion) consisting of Lecturers, Supervisors, Students as Practitioners and the community or related stakeholders. From the findings obtained, the implementation of community development can still be carried out despite the various differences and obstacles encountered in practicum II in the era of the covid-19 pandemic. The most significant difference is related to the existence of Health protocol rules and also the implementation of practicum II in their respective domiciles. As for the obstacles, it is more a matter of limited time and communication between lecturers and practitioners and vice versa.Keywords: Community Development, Practicum II, Covid-19 PandemicAbstrak. Dampak pandemi covid-19 secara disadari merubah berbagai sistem tatanan kehidupan manusia, tidak terkecuali pada lini pendidikan yang merupakan bagian terpenting dari inti manusia. Hal ini juga termasuk pada lini pendidikan bidang kesejahteraan sosial yang berdampak pada pelaksanaan community development yang biasanya dilakukan di tengah-tengah masyarakat atau yang biasa disebut dengan praktikum ii (dua). Meski pada akhirnya, mahasiswa Program Studi Kesejahteraan Sosial UIN syarif hidayatullah jakarta tetap harus dijalankan di masa pandemi covid-19. Oleh karena itu, peneliti ingin melakukan evaluasi terhadap pelaksanaan pelaksanaan community development pada praktikum II mahasiswa kesejahteraan sosial uin syarif hidayatullah jakarta di masa pandemi covid-19.  Penelitian yang menggunakan pendekatan kualitatif ini mencoba melihat dari berbagai sudut pandang informan yang dilakukan dengan cara FGD (Focus Group Discussion) yang terdiri dari Dosen Pengampu, Dosen Pembimbing, Mahasiswa selaku Praktikan dan Masyarakat atau stakeholder yang terkait. Dari temuan yang didapatkan adalah pelaksanaan community development tetap dapat dijalankan meskipun dengan berbagai perbedaan dan kendala yang dihadapi pada praktikum II era pandemi covid-19. Perbedaan yang paling signifikan adalah terkait dengan adanya aturan protokol Kesehatan dan juga pelaksanaan praktikum II di domisili masing-masing. Sedangkan untuk kendala, lebih kepada persoalan waktu yang dirasakan terbatas dan komunikasi baik antara dosen dengan praktikan maupun sebaliknya. Kata kunci: Community Development, Praktikum II, Pandemi Covid-19.